The relationship between small-scale and large-scale ionospheric electron density irregularities generated by powerful HF electromagnetic waves at high latitudes - Tereshcenko, E.D.; Rietveld, Michael T.; Brekke, Asgeir; Khudukon, B.Z.; Isham, B.; Hagfors, T. (European Geosciences Union, 2006)
Satellite radio beacons were used in June 2001 to probe the ionosphere modified by a radio beam produced by the EISCAT high-power, high-frequency (HF) transmitter located near Tromsø (Norway). Amplitude scintillations and variations of the phase of 150- and 400-MHz signals from Russian navigational satellites passing over the modified region were observed at three receiver sites. In several papers it has been stressed that in the polar ionosphere the thermal self-focusing on striations during ionospheric modification is the main mechanism resulting in the formation of large-scale (hundreds of meters to kilometers) nonlinear structures aligned along the geomagnetic field (magnetic zenith effect). It has also been claimed that the maximum effects caused by small-scale (tens of meters) irregularities detected in satellite signals are also observed in the direction parallel to the magnetic field. Contrary to those studies, the present paper shows that the maximum in amplitude scintillations does not correspond strictly to the magnetic zenith direction because high latitude drifts typically cause a considerable anisotropy of small-scale irregularities in a plane perpendicular to the geomagnetic field resulting in a deviation of the amplitude-scintillation peak relative to the minimum angle between the line-of-sight to the satellite and direction of the geomagnetic field lines. The variance of the logarithmic relative amplitude fluctuations is considered here, which is a useful quantity in such studies. The experimental values of the variance are compared with model calculations and good agreement has been found. It is also shown from the experimental data that in most of the satellite passes a variance maximum occurs at a minimum in the phase fluctuations indicating that the artificial excitation of large-scale irregularities is minimum when the excitation of small-scale irregularities is maximum.